Cultural-Educational Activity of the Greek Catholic Bishops in the Establishment of the Ukrainian Language in Transcarpathia (Middle of the ХVІІ – Beginning of the ХХ Century) - Halyna Rozlutska (Pedagogical Discourse, 2017)
The Ukrainians struggle for national self-determination and independence in the historical lands of Transcarpathia is closely connected with the cultural and educational activities of the Mukachevo Greek Catholic bishops. The appearance and development of Ukrainian literary production testifies that the printing in the ethnic Ukrainian lands came from the West, and not from the East. The spread of Western literary monuments included Transcarpathian Ukrainians in the European civilization, and the Ukrainian book provided for the establishment of Ukrainian culture as a component of the national identity of the Ukrainian people.Aspiring to serve the native people, the religious leaders of the period of the Austrian Empire, Parfenius Petrovich, Ioannik Zeykan, Joseph de Camelis, Georgiy Gennadiy Bizantzi, Simeon Olshavskiy, Georgiy Blazhovsky, Ioan Bradach, Manuil Olshavskiy, Andndrey Bachinskiy fought for the cultural rebirth of Transcarpathian Ukrainians based on ethnic patriotism and democratic ideas of European enlightenment. The struggle against imperial centralism and the aggressive pressure on the Greek Catholic clergy on the part of the Roman Catholic clergy created many problems. Hungarian Catholics deliberately destroyed any Ukrainian manifestations, seeing the threat of their power in the national-cultural revival of Transcarpathians.The Mukachevo bishops defended the historic right of Transcarpathian Ukrainians to their native language, taking into account the realities of that time in the Ukrainian lands, which were part of the Austrian Empire and considered the national affair through the prism of faith in the good emperor and moral and Christian ideals. The creation of national school structures contributed to the crystallization of the new generation of Greek Catholic clergy, which was aimed at the formation of national spirituality based on folk culture. The combination of various aspects of ethnic identity – Greek Catholic faith, native language, folk culture and common territory formed the national self-awareness of Ukrainians in Transcarpathia.